Age-matched Z-scores for longitudinal monitoring of center of pressure speed in single-leg stance performance in elite male youth soccer players - Huurnink, A.; Fransz, D. P.; de Boode, V. A.; Kingma, I.; van Dieën, J. H. (The Journal of Strength and Conditioning Research, 2020)
Coordination of corrective motor actions is considered important for soccer performance and injury prevention. A single-leg stance (SLS) test assesses the integrity and proficiency of the sensorimotor control system, quantified by center of pressure averaged speed (COPspeed). We aimed to provide age-matched z-scores for COPspeed in elite male youth soccer players. Second, we assessed a threshold for abnormal long-term change in performance, i.e., critical difference (CD). In a youth academy program, 133 soccer players of 9-18 years were tested twice for both legs (2 repetitions), and one repetition follow-up was conducted at 5.8 months (SD 2.7). Linear regression between age and COPspeed was performed to provide age-matched z-scores. Variance of differences in z-scores at baseline and between sessions was used to estimate the CD up to 5 repetitions. Intraclass correlation coefficients (ICCs) were assessed within and between sessions. The age significantly affected COPspeed (p < 0.0001), with lower values in older players (95% confidence interval; 3.45-9.17 to 2.88-5.13 cm·s-1, for 9 and 18 years, respectively). The z-score CD ranged from 1.72 (one repetition) to 1.34 (5 repetitions). The ICC of z-scores was 0.88 within session and 0.81 between sessions. In conclusion, the SLS performance in elite male youth soccer players improves with age. We determined age-matched z-scores of COPspeed, which reliably determined performance according to age. The CD allows for detection of abnormal variations in COPspeed to identify players with a (temporary) deterioration of sensorimotor function. This could be applied to concussion management, or to detect underlying physical impairments.